TRANSTORNO DO ESPECTRO AUTISTA-TEA: estratégias usadas pelos professores da sala regular com os alunos na Escola Francisco Chagas da Silva – Curralinho - PA - ROMERO, Dieckson Miranda (2024)
This study aims to follow the work of teachers in groups that have autistic students included in the Municipal School of Elementary Education Francisco Chagas da Silva in the city of Curralinho / PA, aiming to make surveys about the methodologies used, difficulties encountered and the relationship between with the autistic student. Qualitative research was based on Bogdan and Biklen (1994), where ethnographic techniques were used, according to André (2012). The analysis of the data obtained in the interviews, questionnaires and logbooks were made taking into consideration Bardin (2011). With this, it is noticed that the way teachers develop their classroom activities with the autistic are based on expository classes in which the students of the class participate in a constant way and that has very positive result for the students' learning, as well as to the relationship between these autistic students and their schoolmates, who come to have a new opinion during the daily school life.